Streptococcal Infections of Fish - Roy Yanong; Ruth Francis-Floyd (EDIS)
This document reviews streptococcal infections in fish, focusing on their identification, impacts, and management strategies. Streptococcus, a Gram-positive bacterium, causes significant mortality in various fish species, with symptoms including erratic swimming, lethargy, exophthalmia, hemorrhages, and rapid deaths. The occurrence of these infections, though less frequent than other bacterial diseases, poses severe financial risks for aquaculture. The review covers historical outbreaks, species affected, and factors contributing to disease onset, such as environmental stressors and compromised water quality. Diagnosis involves identifying Gram-positive cocci in affected tissues, while treatment options include specific antibiotics like erythromycin, amoxicillin, and florfenicol, contingent on sensitivity testing. Preventive measures emphasize maintaining optimal water quality, minimizing stress, and employing vaccines and immunostimulants. Additionally, the document addresses the zoonotic potential of Streptococcus iniae, highlighting the low risk to healthy individuals but cautioning immunocompromised persons. The comprehensive insights provided aim to assist in the effective management and prevention of streptococcal infections in aquaculture settings. First published February, 2002.